Analysis of financial and economic aspects of the companies functioning and their impact on the tourism cluster in the conditions of socialization - Omarova, A.T.; Daniyarova, M.T.; Glazunova, S.B.; Spanova, B.K. (KU Publ., 2022)
Object: In management activity, many companies have to find effective solutions for forecasting and planning various financial scenarios. Effective management of the financial activity of large companies should be based on continuous improvement of business processes, where it is necessary to consider the conditions of the enterprise activity and improve its competitiveness through the consistent implementation of optimization processes and their objective assessment using methods of financial activities forecasting and planning. The research aims to analyze the financial and economic aspects of the companies’ functioning and their impact on the tourism cluster in socialization. Methods: The study was carried out by applying general methods used in economic science, based on a logical description of the components and functions of digital technologies, reflecting their essential properties using a systematic approach, providing the necessary study in depth of the scientific problem. The following methods were used in the research process: abstract-logical, economic-statistical, monographic, methods of system analysis, economic comparison, expert assessments. When processing and organizing the data, methods of mathematical modeling and forecasting were used. The methods used for the study of economic phenomena and the processing of primary information in their entirety make it possible to ensure the reliability of the analysis and the validity of the findings. Findings: The authors reached conclusions and recommendations for improving the sustainable development of companies, results of which were presented using a graphical method. Conclusions: Based on the initial data regression analysis was applied to assess the impact on the amount of income from the main activity of Kazakhstan Temir Zholy JSC of factors such as the volume of passenger traffic and the volume of railway traffic. The coefficients of elasticity are analyzed to supplement the commensurate indicators of the closeness between the factor and the result, allowing ranking of the factors according to the strength of their influence on the result.
Қоғамның әлеуметтенуі жағдайында компаниялар қызметінің қаржы-экономикалық аспектілерін талдау және олардың туристік кластерге әсері
Анализ финансово-экономических аспектов функционирования компаний и их влияние на туристический кластер в условиях социализации общества
Keywords: sustainability; strategy; profitability; tourism cluster; budgeting